KELEMBAGAAN PEMASARAN KOMODITAS JAGUNG DI KAWASAN SENTRA PRODUKSI (THE MARKETING INSTITUTIONAL OF CORN COMMODITY IN THE REGION OF PRODUCTION CENTER) - Anton Parlindungan Sinaga (Inovasi, 2017)
The purpose of this study to determine the Institutional Marketing Commodities Maize Region Production Centers in North Sumatra and to solve various problems related to the institutional marketing of maize in the area of ​​Production Centers. North Sumatera Province as one of agricultural production center area in Indonesia, with main commodity produced one of them is corn. Under the existing conditions along that each institutional marketing of maize is still not running properly marked with yet smooth marketing channel of each subsystem of agribusiness in the area of ​​maize production center in North Sumatra. This happens because the marketing institutions do not work and function in the agribusiness system in corn production centers in North Sumatra. This condition is characterized by the farmers have not been able to receive the proper benefits from the farm business. The type of research is qualitative. The study was conducted in Simalungun, Serdang Bedagai, Karo, Dairi, Langkat and Batubara. Primary data collection was conducted by survey method which was conducted in 6 (six) regencies which is corn production center in North Sumatera. The collected data is then analyzed in order to provide clear information. With a quantitative descriptive format, it is done through an interpretation based on the intellectual understanding constructed by the empirical experience. The analysis used to measure the factors that influence the utilization of corn agribusiness centers by farmers in this study is multiple regression model. Coefficient of predictor age of farmers (X1), educational level (X2), farmers' knowledge about the central region of agribusiness (X5), bond informal farmer with institutional non-region central agribusiness (X6) and the participation of farmers in extension (X7) is positive on the decision Farmers in the utilization of production centers, while the volume of products produced (X3) and farmers living distance to the central region (X4) is negative to the decision of farmers in the utilization of production center. Keywors: institution, maize, production centers